Design and analysis of wrist hand orthosis for carpal tunnel syndrome using additive manufacturing - Jan, Ziaullah; Abas, Muhammad; Khan, Imran; Qazi, Mohsin Iqbal; Jan, Qazi Muhammad Usman (Maǧallaẗ al-abḥath al-handasiyyaẗ, 2025)
Among additive manufacturing (AM) techniques, fused deposition modelling (FDM) is one of the extensively used techniques which add materials layer-by-layer to make three-dimensional parts, unlike subtractive manufacturing which involves the removal of materials. It is widely used in the field of orthotics to build customized products with less material waste and time. This study focuses on a detailed investigation of the designing to manufacturing of FDM-built wrist hand orthosis using nylon material. Patients with carpal tunnel syndrome, a condition caused by compression of the median nerve in the wrist, employ these aids to alleviate their symptoms. First 3D scanning wrist and hand was performed to collect the required data. Which is then further modeled and refined in CAD software’s. Topology optimization was performed to reduce the weight of the wrist hand orthosis. Static analysis of the final design is then performed to evaluate the performance using Von Mises stress, displacement and factor of safety. The results showed that nylon is found to be suitable material for wrist hand orthosis. At 50 N forces the maximum Von Mises Stress developed are 15 MPa which is lower than its yield strength i.e. 42.22 MPa. The maximum displacement produced is also smaller i.e. 0.102 mm, while the minimum safety of factor is 2.82. A carpal tunnel syndrome patient participated in a case study using the Quebec User Evaluation of Satisfaction with Assistive Technology (QUEST) questionnaire to assess satisfaction with a 3D-printed nylon wrist hand orthosis. Results showed relatively good satisfaction and highlighted the orthosis's positive impact on design, lightweight nature, and ease of use.